2021
DOI: 10.1101/2021.11.17.468943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 papain-like protease PLpro in complex with natural compounds reveal allosteric sites for antiviral drug design

Abstract: SARS-CoV-2 papain-like protease (PLpro) covers multiple functions. Beside the cysteine-protease activity, PLpro has the additional and vital function of removing ubiquitin and ISG15 (Interferon-stimulated gene 15) from host-cell proteins to aid coronaviruses in evading the host’s innate immune responses. We established a high-throughput X-ray screening to identify inhibitors by elucidating the native PLpro structure refined to 1.42 Å and performing co-crystallization utilizing a diverse library of selected nat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Three phenolic compoundsmethyl 3,4-dihydroxybenzoate (HE9, 20 ), 4-(2-hydroxyethyl)­phenol (YRL, 21 ), and 4-hydroxybenzaldehyde (HBA, 22 )were identified as allosteric SARS-CoV-2 PL pro inhibitors through a high-throughput X-ray crystallization . The screened library contains 500 compounds from the International Center for Chemical and Biological Sciences (ICCBS) Molecular Bank.…”
Section: Sars-cov-2 Plpro Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three phenolic compoundsmethyl 3,4-dihydroxybenzoate (HE9, 20 ), 4-(2-hydroxyethyl)­phenol (YRL, 21 ), and 4-hydroxybenzaldehyde (HBA, 22 )were identified as allosteric SARS-CoV-2 PL pro inhibitors through a high-throughput X-ray crystallization . The screened library contains 500 compounds from the International Center for Chemical and Biological Sciences (ICCBS) Molecular Bank.…”
Section: Sars-cov-2 Plpro Inhibitorsmentioning
confidence: 99%
“… 52 This site is also the drug-binding site for GRL0617 ( 4 ) and its analogues. 16 The X-ray crystal structures for the apo SARS-CoV-2 PL pro , drug-bound form, 52 55 and complex forms with ubiquitin ( Figure 2 A) and ISG15 ( Figure 2 B) have been solved, 56 paving the way for structure-based drug design and understanding the virology of PL pro .…”
Section: Introductionmentioning
confidence: 99%
“…Others also identified 6-thioguanine and 6-mercaptopurine ( Sivakumar and Stein, 2021 ; Swaim et al, 2021 ), which were later invalidated as either inactive or toxic in follow-up cellular assays ( Ma and Wang, 2022 ). Finally, a number of naturally occurring compounds were also highlighted ( Srinivasan et al, 2021 ) for their activity as allosteric inhibitors of PLpro (preprint at the time of writing this Review). Structures of these ( Figure 1 ) highlighted that they inhibit substrate binding at the S2 site of PLpro, a feature not yet seen for any PLpro inhibitors.…”
Section: Overview Of the Plpro Inhibitor Binding Sitementioning
confidence: 99%
“…Here we considered additional PLpro binders from the protein data bank. Among these, three recently described phenolic fragments were further analyzed and included in the compound extensions ( Srinivasan et al, 2021 ), as they were found in adjacent binding positions of the S2 site of SARS-CoV-2 PLpro and show partial overlap with our ligands ( Supplementary Figure S5 ). 4-(2-hydroxyethyl)-phenol (YRL; PDB: 7ofs) and 4-hydroxybenzaldehyde (HBA; PDB: 7oft) bind in a pocket next to the phenol moiety of the thiosemicarbazones T1-T5 ( Supplementary Figures S5B, S5C ).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in binding energies between the thiosemicarbazones, caused by the individual phenolic substitution patterns, were reduced for the compound extension by the addition of the second phenol ring. As a result, the extended compounds will most likely not only possess an increased binding affinity but also an increased inhibitory potential as the separate phenolic fragments alone were already shown to inhibit deubiquitination by PLpro ( Srinivasan et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%